The Latin American Spanish version of the Face-Name Associative Memory Exam is sensitive to cognitive and pathological changes in preclinical autosomal dominant Alzheimer's disease (2020)
ABSTRACT: Background: To determine whether performance on the Latin American Spanish version of the Face-Name Associative Memory Exam (LAS-FNAME) can differentiate between cognitively intact carriers of an autosomal dominant Alzheimer's disease mutation (E280A) in Presenilin-1, who are genetically determined to develop early-onset dementia, from matched non-carriers. We also sought to examine whether LAS-FNAME performance is associated with amyloid-β and regional tau burden in mutation carriers. Methods: A total of 35 cognitively intact mutation carriers (age range 26-41), 19 symptomatic carriers, and 48 matched non-carriers (age range 27-44) completed a neuropsychological assessment including the LAS-FNAME. A subset of participants (31 carriers [12 symptomatic] and 35 non-carriers) traveled from Colombia to Boston to undergo positron emission tomography (PET) using Pittsburgh compound B to measure mean cortical amyloid-β and flortaucipir for regional tau. ANOVA analyses and Spearman correlations were used to examine group differences and relationships among LAS-FNAME performance and amyloid-β and tau accumulation. Results: Compared to non-carriers, cognitively intact mutation carriers had lower scores on the LAS-FNAME Total Scores (p = .040). Across all carriers (including symptomatic carriers), higher levels of amyloid-β (r = - .436, p = .018) and regional tau in the entorhinal (r = - .394, p = .031) and inferior temporal cortex (r = - .563, p = .001) were associated with lower LAS-FNAME Total Scores. Conclusions: Performance on the LAS-FNAME differentiated between cognitively intact mutation carriers from non-carriers and was associated with greater amyloid and tau burden when examining all carriers. Findings suggest that the LAS-FNAME is sensitive to early clinical and pathological changes and can potentially help track disease progression in Spanish-speaking individuals. Keywords: Alzheimer’s disease; Associative memory; Autosomal dominant Alzheimer’s disease; Imaging; Neuropsychology; PET.